2021
DOI: 10.1186/s12913-021-07234-1
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of emotional competence on job satisfaction and organisational commitment of healthcare professionals

Abstract: Background Healthcare organisations, such as hospitals, are largely seen as task-oriented, width different people expected to work in interdependent teams. The objective of this study was to investigate the relevance of individual factors (job satisfaction) and individual competences (emotional competence) for organisational commitment in a sample of healthcare professionals. Methods A cross-sectional survey was conducted among 96 healthcare profes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The association observed between job satisfaction and wellbeing (as well as turnover intentions), irrespective of wellbeing centre use, supports the need for strategies to enhance job satisfaction in HCWs. Many approaches have shown promise; studies have accentuated the influence of empowerment and transformational leadership [ 102 ] and emotional competence [ 103 , 104 ] on job satisfaction among HCWs. Participation in ‘Compassion Rounds’ has shown to increase job satisfaction, by fostering emotional expression, teamwork, and communication [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association observed between job satisfaction and wellbeing (as well as turnover intentions), irrespective of wellbeing centre use, supports the need for strategies to enhance job satisfaction in HCWs. Many approaches have shown promise; studies have accentuated the influence of empowerment and transformational leadership [ 102 ] and emotional competence [ 103 , 104 ] on job satisfaction among HCWs. Participation in ‘Compassion Rounds’ has shown to increase job satisfaction, by fostering emotional expression, teamwork, and communication [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…A healthcare professional study has shown that emotional competence tends to correlate with the job satisfaction and organizational commitment. It also concludes that healthcare professionals with emotional competence can remain their organizational commitment unaffected while they deal with dissatisfaction in the workplace [27]. In Northwest Haiti a study was conducted and concluded that there is a strong positive correlation between affective commitment and job satisfaction.…”
Section: Correlation Of Job Satisfaction and Organizational Commitmentmentioning
confidence: 99%
“…Emotional aspects in organizational settings are studied in numerous contexts, and there is evidence that EC is related to organizational outcomes such as job satisfaction, well-being (Miao et al., 2017; Sánchez-Álvarez et al, 2016), health, burnout (Fiorilli et al, 2019; Martins et al, 2010), job performance (Joseph et al, 2015; O'Boyle et al., 2011), and organizational commitment (Stamouli & Gerbeth, 2021). In addition, EC received interest in the educational context (Petrides et al, 2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%